2017
DOI: 10.1016/j.molp.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Roles of PIFs in Signal Integration from Multiple Processes

Abstract: PHYTOCHROME INTERACTING FACTORs (PIFs) are members of the basic helix-loop-helix (bHLH) family of transcription factors in Arabidopsis. Since their discovery in phytochrome-mediated light signaling pathways, recent studies have unraveled new functions of PIFs in integrating multiple signaling pathways not only by their role as transcription factors directly targeting gene expression, but also by interacting with diverse groups of factors to optimize plant growth and development. These include endogenous (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
171
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 94 publications
2
171
0
Order By: Relevance
“…Thus, having multiple kinases and E3 ubiquitin ligases might allow fine-tuning the rate of degradation and the sensitivity to different fluences. Second, PIFs are not involved only in light signaling pathways, but recent studies highlight the importance of PIFs in multiple aspects of plant growth and development and response pathways (Leivar and Monte, 2014;Paik et al, 2017). Thus, PIFs act as a central hub in many cellular signaling pathways (e.g.…”
Section: E3 Ligases For Pifsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, having multiple kinases and E3 ubiquitin ligases might allow fine-tuning the rate of degradation and the sensitivity to different fluences. Second, PIFs are not involved only in light signaling pathways, but recent studies highlight the importance of PIFs in multiple aspects of plant growth and development and response pathways (Leivar and Monte, 2014;Paik et al, 2017). Thus, PIFs act as a central hub in many cellular signaling pathways (e.g.…”
Section: E3 Ligases For Pifsmentioning
confidence: 99%
“…Thus, PIFs act as a central hub in many cellular signaling pathways (e.g. GA, brassinosteroid [BR], auxin, ethylene, JA, circadian, and many others; Leivar and Monte, 2014;Paik et al, 2017). Therefore, signaling factors from these pathways (e.g.…”
Section: E3 Ligases For Pifsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PHY and CRY photoreceptors can physically interact with specific sets of PIF proteins and thereby regulate PIF phosphorylation. The phosphorylation status of PIFs subsequently determines their activity and in most instances their stability (Paik et al, 2017). ChIP-seq studies on PIFs have identified a very broad range of target genes, including those associated with cell wall modifications, auxin biology and several other transcription factors.…”
Section: Pifsmentioning
confidence: 99%